Investigations into structure-property relationships of novel Ru(II) dyes with N, N′-Diethyl group in ancillary ligand for dye-sensitized solar cells. (December 2019) - Ashraf, Saba; Su, Rui; Akhtar, Javeed; Siddiqi, Humaira M.; Shuja, Ahmed; Al-Saad, Khalid A.; Al-Qaradawi, Siham Y.; El-Shafei, Ahmed
Abstract: Structure-property relationships of four novel bipyridyl Ru(II) complexes, denoted as SD-22, SD-24, SD-26 and SD-28, are reported herein. The molecular structures of all four photosensitizers were confirmed using FT-IR, 1 H NMR and mass spectrometry. Photovoltaic characteristics of the photosensitizers were evaluated under 1.5 a.m. standard illumination condition, in presence of deoxycholic acid as co-adsorbent, and subsequently compared to the performance of the benchmark, Z907. SD-22 showed an IPCE of 52% and 50% at 440 nm and 550 nm, respectively, a short-circuit photocurrent density ( J SC ) of 17.37 mA cm −2, open-circuit photovoltage ( V OC ) of 0.63 V and fill factor ( FF ) of 0.66, producing an overall conversion efficiency ( η ) of 7.31%, which outperformed Z907 (7.02%) under the same experimental device conditions. The η of the other photosensitizers is in the following order: SD-22 > SD-28 > SD-26 > SD-24. Photosensitizer SD-22 has N, N′ -dialkyl group attached to a benzene ring while SD-24 has N, N′-dialkyl without a benzene ring. The extended conjugation in SD-22 translated into higher overall solar-to-electric conversion efficiency. Substitution of dialkylamino-based ancillary ligands of Ru(II) dyes SD-26 and SD-28 with –OCH3 and –OC6 H13 also demonstrated that the photovoltaic performance of polypyridyl ruthenium photosensitizers is a function of the donating power of ancillary ligands as well as the steric effect of alkoxy auxochromes at – ortho position. Highlights: Structure-property relationship of four bipyridyl Ru(II) complexes with N, N′ -diethyl group in ancillary ligand was studied. Highlights the effect of extended conjugation on the photocurrent and photovoltage in DSSC. SD-22 outperformed the rest of the dyes in photovoltaic performance due to better light-harvesting ability. Enhancement of the photovoltaic performance in SD-22 is ascribed to the presence of aromatic ring and smaller alkyl chains. Molecular modulations of electron donating N, N′ -diethyl based Ru(II) dyes was presented to further analyze the properties.